Navigating the Future: Trends and Innovations in the Development of Business and Management Education - Zahroh, Ainun; Pratiwi, Galuh Aulia; Wardana, Ludi Wishnu; Murwani, Fulgentius Danardana; Wati, Andy Prasetyo (Journal of Applied Business, Taxation and Economics Research, 2024)
The latest trends in global business education and innovations that are changing teaching and learning paradigms. It is hoped that the findings from this research will provide in-depth insight into how business and management education can continue to develop and be relevant in an era that continues to change rapidly, as well as provide recommendations for improving the quality of global business education. It is hoped that this research can make a significant contribution to the development of curricula, teaching methods, and management strategies for business education in the future. This research uses the Systematic Literature Review (SLR) method by collecting and analyzing journals related to keywords. Based on the literature study conducted, the importance of the ability to identify and anticipate the latest trends and innovations in business and management education was found. Through in-depth analysis of innovative teaching methods and effective educational management strategies, this research helps build a strong foundation for the development of relevant, high-quality curricula. Thus, this research not only provides a better understanding of the dynamics of global business education but also supports efforts to improve the quality of graduates who are ready to face future business challenges.